Mićo Ljubibratić, the first interpreter of the Qur’an in our speaking area - Ujkanović Enver (Glasnik Etnografskog Instituta SANU, 2020)
Legitimacy of the Qur’an translation to non-Arabic languages has never been disputable nor religiously forbidden act during the initial period of Islam for a great number of researchers. Initiators of the debate about the Qur’an translation and the legitimacy of that act were ‘non- Arabs’ -’ağam, who believed that they can only relatively apprehend the divine holy discourse - Qur’an, as they were limited by their own mother tongue. According to historical sources, there were no initiatives to translate Qur’an in our speaking area before the 19th century. The process of the Qur’an translation, however, has started in 1895 with Mićo Ljubibratić. In this paper the motifs of Ljibibratić’s work are analysed, as well as the absence of early translations among the adherents of Islam. The paper then reflects on the response to the Ljubibratić’s translation and the influence of his work upon the translation activity among the adherents of Islam. The other part of the paper is based on a contrastive lexical semantic analysis of the translation of Qur’an lexis excerpted from Quranic passages (Surah and Ayahs). The comparison between the Ljubibratić’s translation and the later translations of the Qur’an, as for example the translation from Arabic by Besim Korkut, shows differences on the semantic level, and allow us to observe the development and evolution of the experience in translating the Qur’an in our speaking area.